2010
DOI: 10.1016/j.ejcts.2010.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate results following complex biventricular repair of left ventricular outflow tract obstruction in neonates and infants☆

Abstract: Complex biventricular repair can be performed in neonates and infants with severe LVOTO with mid-term survival that is equivalent to that published following balloon or surgical aortic valvotomy. Associated lesions are significant factors that influence outcome and proper patient selection may further improve survival. In neonates with concomitant arch obstruction and VSD, the Yasui operation may be associated with lower early mortality risk. Neonates with concomitant mitral valve pathology may be better serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 21 publications
2
19
0
2
Order By: Relevance
“…7,19 Infants and neonates are particularly at highest risk of operative death, especially when simultaneous arch and mitral intervention is needed. 7,20,21 In our current series, we demonstrated that the Ross procedure can be safely performed in older children with rheumatic valve disease with no operative mortality despite that many of the patients required concomitant mitral valve repair.…”
Section: Discussionmentioning
confidence: 65%
“…7,19 Infants and neonates are particularly at highest risk of operative death, especially when simultaneous arch and mitral intervention is needed. 7,20,21 In our current series, we demonstrated that the Ross procedure can be safely performed in older children with rheumatic valve disease with no operative mortality despite that many of the patients required concomitant mitral valve repair.…”
Section: Discussionmentioning
confidence: 65%
“…Операция стала широко применяться специалистами, и, как следствие, расширились показания к ее осуществле-нию. Мировой опыт показывает, что условиями клини-ческой эффективности при выполнении операции Росса являются: прецизионный забор аутографта и сохране-ние первой септальной ветви левой коронарной артерии; корректная имплантация аутографта с соблюдением раз-мерного соответствия диаметров легочного аутографта и фиброзного кольца аорты; профилактика перегибов и деформаций зоны имплантации коронарных артерий в аутографт; исключение повреждения и деформации левой коронарной артерии при имплантации клапаносодержа-щего кондуита в выводной тракт правого желудочка [13].…”
Section: особенности процедуры россаunclassified
“…ким риском быстрой структурной дегенерации клапанов и их ранней кальцификацией. Более того, у специалистов не всегда имеются в наличии нужные размеры гомограф-тов и биопротезов при выполнении вмешательств [7,13].…”
unclassified
“…If the native left ventricular outflow tract cannot be used as the sole systemic outflow, it needs to be replaced by a Ross or a Ross-Konno operation or augmented with a Damus-Kaye-Stansel procedure, as in the Yasui operation if a VSD is present [2]. The neonatal Ross operation is associated with high mortality, especially when associated with arch repair [3,4]. Furthermore, the Yasui operation can be performed as a single stage or as a staged repair (Norwood-Rastelli).…”
mentioning
confidence: 99%